Single-stranded RNA phages : from molecular biology to nanotechnology - Pumpens, Paul (Boca Raton, FL : CRC Press, 2020)
This is a comprehensive guide to single-stranded RNA phages (family Leviviridae), first discovered in 1961. These phages played a unique role in early studies of molecular biology, the genetic code, translation, replication, suppression of mutations. Special attention is devoted to modern applications of the RNA phages and their products in nanotechnology, vaccinology, gene discovery, evolutionary and environmental studies. Included is an overview of the generation of novel vaccines, gene therapy vectors, drug delivery, and diagnostic tools exploring the role of RNA phage-derived products in the revolutionary progress of the protein tethering and bioimaging protocols. Key Features Presents the first full guide to single-stranded RNA phages Reviews the history of molecular biology summarizing the role RNA phages in the development of the life sciences Demonstrates how RNA phage-derived products have resulted in nanotechnological applications Presents an up-to-date account of the role played by RNA phages in evolutionary and environmental studies
OCLC-licensed vendor bibliographic record.
Keywords: RNA viruses; Bacteriophages; Molecular biology; Nanotechnology; Viruses -- Evolution; SCIENCE / Life Sciences / Cytology; SCIENCE / Life Sciences / Biology / Microbiology; SCIENCE / Life Sciences / Biology / Molecular Biology